Insomnia and Female Reproductive Diseases: A Cross-Sectional and Mendelian Randomization Study - Fang L; Wang Y; Wang R; Fang Y; Xie Y; Yang S; Liu S; Zhang Y (International Journal of Women's Health)
Liyuan Fang,1,* Yan Wang,1,* Runxi Wang,1 Yuhang Fang,2 Yi Xie,2 Shuhan Yang,2 Suying Liu,1 Ying Zhang1 1Department of Oncology, Guang’anmen Hospital of the Chinese Academy of Traditional Chinese Medicine, Beijing, People’s Republic of China; 2Graduate School, Beijing University of Chinese Medicine, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ying Zhang, Department of oncology, Guang’anmen Hospital of the Chinese Academy of Traditional Chinese Medicine, Beijing, 100053, People’s Republic of China, Email zylzy501@163.comBackground: Insomnia is increasingly emerging as a significant concern in public health, with a longstanding emphasis on its relationship with overall well-being. Nevertheless, few research has been devoted to investigating the relationship between insomnia and female reproductive health.Methods: In our study, we conducted a Mendelian randomization (MR) study to estimate the causal relationship between insomnia and female reproductive diseases. A total of 268 independent genetic variants associated with insomnia at the genome-wide significance level (P < 5× 10− 8) were used as instrumental variables. Summary-level data were obtained from the UK Biobank and Finn Gen study, including ovarian cysts, polycystic ovarian syndrome (PCOS), endometriosis, premature ovarian insufficiency (POI), ovarian cancer (OC), uterine fibroids, endometrial cancer (EC) and female infertility. We performed logistic regression to assess the associations between insomnia and the risk of OC and EC by using data from the National Health and Nutrition Examination Survey (NHANES) 2013– 2014.Results: Our research reveals that genetic liability to insomnia constitutes a risk factor for ovarian cysts (odds ratio [OR]: 1.44, 95% confidence interval [CI]: 1.21– 1.72, P< 0.05), PCOS (OR: 1.67, 95% CI: 1.44– 1.94, P< 0.05), and endometriosis (OR: 1.43, 95% CI: 1.16– 1.76, P< 0.05). However, we found no statistically significant associations between insomnia and POI, OC, uterine fibroids, EC, or female infertility. Additionally, body mass index (BMI) was found to mediate about 10% of the effect of the insomnia on ovarian cysts and PCOS. Moreover, in cross-sectional study, insomnia was not associated with OC and EC.Conclusion: Our study provides causal evidence that genetically predicted insomnia increases the risk of ovarian cysts, PCOS, and endometriosis. Accordingly, the potential significance of weight control and good sleep in keeping fit need to be emphasized.Keywords: Mendelian randomization, insomnia, ovarian cysts, polycystic ovarian syndrome, endometriosis